Epidemiological characterization of leprosy in the North and Northeast regions of Brazil (Research, Society and Development, 2020)
Objective: to evaluate the epidemiological profile of leprosy in the North and Northeast regions of Brazil between the years 2015 and 2018. Methodology: this is a descriptive, retrospective epidemiological research with a quantitative approach. The data show the epidemiological characterization regarding sex, age group and operational classification of confirmed cases of leprosy in the North and Northeast regions of Brazil between the years 2015 and 2018. Results: the evaluation of the epidemiological data showed a total of 63,051 diagnosed cases of leprosy in the North and Northeast regions in the analyzed period. When investigating the profile of confirmed leprosy cases, it was observed that 56% occurred in males, the age group most affected was 35 to 49 years, equivalent to 28% of cases, followed by individuals aged 50 to 64 years (25 %) and 20 to 34 years old (20%) and the most incident operational classification was the multibacillary (74%). Conclusion: the findings reflect the need for continuous training of health professionals who provide assistance to patients with leprosy and the strengthening of surveillance and epidemiological control actions.